PENINGKATAN PANGSA PASAR DALAM PERUSAHAAN MARKETPLACE MELALUI CUSTOMER SATISFACTION - FLORENSIA, LISA; SUTRISNO, NUNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted to determine the influence of Utilitarian Values. Hedonic Value, Social Value, and Perceived Risk on Customer Satisfaction among Bukalapak application users in Bekasi City. The research method used in this research was a survey. Data analysis in research uses quantitative and uses a causal research plan. The sampling method in this research used Non-Probability Sampling with Purposive Sampling technique. Variable measurement uses a 5 point Likert scale. This research uses primary data, where all data samples were obtained through distributing questionnaires totaling 122 respondents, and processed using SPSS version 25. The data analysis technique used in this research is multiple linear regression. The results of this research show that Utilitarian Value, Hedonic Value, Social Value and Perceived Risk have a significant influence on Customer Satisfaction among Bukalapak application users in Bekasi City.